MOTIVASI PENGUNJUNG KE TAMAN KOTA TUNJUK AJAR INTEGRITAS DI KOTA PEKANBARU - Chaira Maulida; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the city of Pekanbaru. The purpose of this research is to find out what are the motivations of visitors to the Park City Point's learning Integrity in the city of Pekanbaru. The focus of this research topic is to know what are the functions of Integrity Teaching Point City Park in the city of Pekanbaru. The technique of determination of samples in Accidental Sampling. The number of samples in the study conducted is 13 people. The author uses descriptive qualitative methods and instruments of data are observation, interview and documentation. Research conducted to find: research finds the motivation of visitors to the Park City Point's learning Integrity is as follows: Leisure, visitors coming from different ages. But most who come are family who brought her son to play. Discussion, research found that visitors who come to the City Park in addition to the leisure they also come for the purpose of discussion. Learning activities, research found that the other thing that became the motivation for visitors to come to the Park City Point's learning integrity is for learning activities. For students in all schools, in addition they certainly also need places to learn outside of the room. Thus, they come to the Park to take advantage of the existing facilities as a place to learn. Trade, research found that visitors who come not only for leisure, learning and discussion but nothing came to trade. They sell food and drink, even renting out toys to visitors. They sell using carts on the roads around the Park area of the city Point's learning integrity.Keywords: Motivation, City Parks, Open Green Space